Remediation of heavy metal contaminated soil by asymmetrical alternating current electrochemistry - Jinwei Xu (Nature Portfolio, 2019)
Soil pollution by heavy metals is a problem of global concern, requiring the development of remediation technologies. Here the authors report a method based on asymmetrical alternating current electrochemistry, which enables recycling of soil washing chemicals and eliminates secondary pollution.